2004
DOI: 10.1073/pnas.0307948101
|View full text |Cite
|
Sign up to set email alerts
|

Responses of human visual cortex to uniform surfaces

Abstract: Surface perception is fundamental to human vision, yet most studies of visual cortex have focused on the processing of borders. We therefore investigated the responses of human visual cortex to parametric changes in the luminance of uniform surfaces by using functional MRI. Early visual areas V1 and V2͞V3 showed strong and reliable increases in signal for both increments and decrements in surface luminance. Responses were significantly larger for decrements than for increments, which was fully accounted for by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
62
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 30 publications
(39 reference statements)
19
62
2
Order By: Relevance
“…These results are not in accord with the previous studies, which indicated activation in areas including V2, V3͞VP, V3A, and V4v (39)(40)(41)(42)(43). Why does this discrepancy occur?…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are not in accord with the previous studies, which indicated activation in areas including V2, V3͞VP, V3A, and V4v (39)(40)(41)(42)(43). Why does this discrepancy occur?…”
Section: Methodscontrasting
confidence: 99%
“…The spatially global nature of the activity for the filling-in only in V1 suggests that long-range horizontal connections in V1 (53), which previously have been found only with contour signals and edges (53), may occur even with non-contour-based feature signals such as colors and brightness. The result of the activity with the uniform disk stimulus in experiment 3 is basically the same as that with color filled-in transparency in experiment 1 and also is in accord with the recent finding that V1 activity in response to a uniform surface is the highest in early visual areas (43). These results suggest that long-range horizontal connections are involved in both the color filling-in processing and uniform surface processing.…”
Section: Discussionsupporting
confidence: 89%
“…Stanley and co-workers 26 reconstructed natural movies by modeling the luminance of individual image pixels as a linear function of single-unit activity in cat LGN. This approach assumes a linear relationship between luminance and the activity of the recorded units, but this condition does not hold in fMRI 27,28 .…”
mentioning
confidence: 99%
“…An fMRI study by Goodyear & Menon (1998) reported that cortical activity in the primary visual cortex increased in the volume of regional activation, as well as activation intensity, as the luminance intensity increased. Furthermore, they reported a close relationship between perceived brightness contrast and responses in the primary visual cortex (e.g., Haynes, Lotto, & Rees, 2004;Osaka & Yamamoto, 1978;Wicke, Donchin, & Lindsley, 1964). Wicke et al (1964) showed that VEP peak latency varies with stimulus luminance and higher luminance yields faster latency.…”
mentioning
confidence: 95%
“…Wicke et al (1964) showed that VEP peak latency varies with stimulus luminance and higher luminance yields faster latency. An fMRI study by Haynes, et al (2004) showed that the blood oxygenation level-dependent (BOLD) signals in the early visual cortex scaled linearly with the magnitude of change in retinal illumination, simultaneously correlating with subjective ratings of perceived brightness. These results indicate that perceived brightness may be encoded in the primary visual cortex.…”
mentioning
confidence: 99%